Reformulating the Educational Philosophy and Aim of LPTK (Teacher Training Institutions) in Indonesia - Suwirta, Andi; Purwanto, Joko (EDUCARE, 2013)
ABSTRACT: Entering the 21st century, there was a new phenomenon in higher education world in Indonesia, especially for institution of education and teacher training. In 2000, for example, ten IKIPs (Institut Keguruan dan Ilmu Pendidikan or Institute of Education and Teacher Training) in Indonesia changed their names into university. Accordingly, discussing critically educational philosophy and aim in a nation-state is very important and should always be sought for in order to realize the critical society, especially related to the question of how this nation-state will be built. Every nation-state has contextual education philosophy and aim, which is particular in its own historical and social context. Indonesia, as a nation-state, has unique educational philosophy and aim, and it is the next generationâs job to revitalize and implement it in the real educational praxis. This paper tries to discuss the position and role of LPTK (Lembaga Pendidikan Tenaga Kependidikan or Teacher Training Institutions) as one of higher educational institutions that is responsible to educate the professional teachers in Indonesia. It is imperative to reformulate and revitalize the educational philosophy and aim of LPTK, especially related to preparing the candidate of such institution participants â who will be the teachers and educators in the future â in order that educational development in Indonesia can educate the people in one side, and can strengthen self identity in other side as civilized, advanced, modern, prosperous, and social justice nation. KEY WORDS: National philosophy, educational aim, teacher training institutions, and reformulate the position and role of institution.Â Â Â About the Authors: Andi Suwirta, M.Hum. is a Senior Lecturer at the Faculty of Social Studies Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java; and Joko Purwanto, M.Pd. is a Senior Lecturer at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuh Waluh, Purwokerto, Central Java, Indonesia. They can be reached at: aspensi@yahoo.comHow to cite this article? Suwirta, Andi & Joko Purwanto. (2013). âReformulating the Educational Philosophy and Aim of LPTK (Teacher Training Institutions) in Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.5(2) February, pp.191-200. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 27, 2012); Revised (January 30, 2013); and Published (February 17, 2013).Â  Â